Pengaruh Volume Penjualan Saham, Profitabilitas, Solvabilitas, Earning Volatility dan Tranding Volume terhadap Volatilitas Harga Saham dengan Kebijakan Deviden sebagai Variabel Mediasi - Romadhany, Desvyana; Kusumawardhani, Ratih; Rinofah, Risal (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the effect of share sales volume, profitability, solvency, earnings volatility and trading volume on share price volatility with dividend policy as a mediating variable in food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample for this research consisted of 55 companies, using a purposive sampling method with the criteria stating dividend payments for 5 consecutive years. The research results show that debt ratio, return on assets, trading volume have an influence on stock price volatility. However, earnings volatility and share sales volume have no effect on share price volatility. Dividend policy is able to mediate share sales volume on stock price volatility, dividend policy is able to mediate profitability on stock price volatility, dividend policy is able to mediate solvency on stock price volatility, dividend policy is able to mediate earnings volatility on stock price volatility and dividend policy is able to mediate volume trending on stock price volatility in food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2021 period.